2016
DOI: 10.15252/embr.201642486
|View full text |Cite
|
Sign up to set email alerts
|

PARylation of the forkhead‐associated domain protein DAWDLE regulates plant immunity

Abstract: Protein poly(ADP-ribosyl)ation (PARylation) primarily catalyzed by poly(ADP-ribose) polymerases (PARPs) plays a crucial role in controlling various cellular responses. However, PARylation targets and their functions remain largely elusive. Here, we deployed an Arabidopsis protein microarray coupled with in vitro PARylation assays to globally identify PARylation targets in plants. Consistent with the essential role of PARylation in plant immunity, the forkhead-associated (FHA) domain protein DAWDLE (DDL), one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 39 publications
0
36
0
Order By: Relevance
“…Using a forward genetic screen based on flg22-induced gene transcriptional change, protein poly(ADP-ribosyl)ation (PARylation), which is reversibly regulated by poly(ADP-ribose) polymerases (PARPs) and poly(ADP-ribose) glycohydrolases (PARGs), was indicated to play a role in regulating MAMP-responsive gene expression (41). flg22 treatment induces the PARylation of the forkhead-associated domain protein DAWDLE, a substrate of Arabidopsis PARP2, to regulate some of late PTI responses (42). It is postulated that PARylation of DDL may induce chromatin remodeling that creates a permissive chromatin environment for RNAPII-mediated transcription of MAMP-responsive genes.…”
Section: Early Pattern Recognition Receptor Signaling Eventsmentioning
confidence: 99%
“…Using a forward genetic screen based on flg22-induced gene transcriptional change, protein poly(ADP-ribosyl)ation (PARylation), which is reversibly regulated by poly(ADP-ribose) polymerases (PARPs) and poly(ADP-ribose) glycohydrolases (PARGs), was indicated to play a role in regulating MAMP-responsive gene expression (41). flg22 treatment induces the PARylation of the forkhead-associated domain protein DAWDLE, a substrate of Arabidopsis PARP2, to regulate some of late PTI responses (42). It is postulated that PARylation of DDL may induce chromatin remodeling that creates a permissive chromatin environment for RNAPII-mediated transcription of MAMP-responsive genes.…”
Section: Early Pattern Recognition Receptor Signaling Eventsmentioning
confidence: 99%
“…Most recently, Feng and coworkers demonstrated that PARP2 participates in important reactions with DAWDLE (DDL), a forkhead-associated (FHA) domain protein. The PARylation-dependent interaction between PARP2 and DDL is essential to the function of DDL in plant immunity (207).…”
Section: Plant Parpsmentioning
confidence: 99%
“…While early immune signalling events are unaffected in dll mutants, defence gene expression and callose deposition are reduced, indicating a role in late immune response. Feng et al also show that the double mutant parp1/2 phenocopies the immunity phenotypes of dll mutants, tightening the link between the requirement for PARPs, PARylation and DLL in late immunity.…”
Section: Hypothetical Poly(adp‐ribose) Decoding System For Plant Immumentioning
confidence: 93%
“…In plants, however, mechanistic understanding of the role of ADP ‐ribosylation in stress response is still lacking. In this issue of EMBO Reports, Feng et al identify the first set of PAR ylated plant proteins and show that in vivo PAR ylation of one of these proteins, a factor named DAWDLE , is important for its role in plant immunity.…”
mentioning
confidence: 99%